Effects of different HTO correction angles on ankle joint biomechanics in 3D varus knee model: a patient-specific simulation study - Yinghui Zhu; Adeel Anwar; Mengke Ren; Yufang Zhang; Weiguo Zhang; Zhen Zhang (Frontiers in Bioengineering and Biotechnology, 2026)
Objective The mechanical axis in the varus knee deteriorates normal ankle joint biomechanics. Consequently, degrees of correction angles may also alter ankle stresses. This study aimed to elaborate the stress changes in articular cartilages and pressure in the subtalar joint of the ankle joint using finite element analysis (FEA) with different osteotomy correction angles. Methods Computed tomography and magnetic resonance images were propagated to get a full leg model that included the knee and ankle joints. Computer-aided design (CAD) software was used to simulate osteotomy. Then, correction axes were carried out. Osteotomy gaps were filled to mimic bone healing. Model A represents the varus knee. Models B, C, D, and E represent osteotomy models with a neutral axis and 3.5°, 5.5°, and 7.5° over-corrected valgus angles, respectively. Simulated loads were applied to the femoral head. Results The mean stress in tibial cartilage (71.69 MPa) in model A was significantly reduced to 36.17 MPa, 34.55 MPa, 34.14 MPa, and 32.25 MPa in high tibial osteotomy (HTO) correction models B, C, D, and E, respectively ( p < 0.001). Contrarily, the mean von Mises stress (VMS) of 23.81 MPa in model A was reduced to 19.74 MPa and to 18.60 MPa in models C and D, respectively ( p < 0.05) in talar cartilage. The shear stress analysis of tibial cartilage showed that the peak shear stress of 8.289 MPa was reduced to 5.203 MPa in the neutral axis model ( p < 0.05) and further decreased to 4.639 MPa, 4.569 MPa, and 4.666 MPa in models with a neutral axis and 3.5°, 5.5°, and 7.5° valgus ( p < 0.05), respectively. The subtalar joint pressure was higher in over-corrected models with 5.5° and 7.5° valgus angles ( p < 0.05), but in the 3.5° valgus model, this increase was non-significant ( p > 0.05). Conclusion The varus knee model and its corrective osteotomy had a definitive impact on the ipsilateral ankle joint and the hindfoot. Ankle joint stresses were significantly reduced in the 3.5° valgus model. Subtalar pressure was lateralized in varus models, whereas it was medialized in valgus correction models. Surgeons should consider these compensatory ankle joint biomechanical alterations before planning HTO.